2005
DOI: 10.1007/s00024-004-2647-6
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Ambient Noise Horizontal-to-Vertical Spectral Ratio in Urban Environments: The Case of Thessaloniki City (Northern Greece)

Abstract: In the framework of an ambient noise measurement project in the downtown district of the City of Thessaloniki (Northern Greece), several tests and evaluation of noise recordings were performed in selected sites. This data set was processed and compared with previous results for the same sites in terms of horizontal-to-vertical (H/V) spectral ratio obtained from weak and strong motion earthquake data. The recording system used was tested against a reference one. Finally, systematic ambient noise measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 44 publications
6
12
0
Order By: Relevance
“…The study area reflects a high variability in terms of fundamental frequency f 0 and alluvium thickness H. Overall results reflect low values of fundamental frequency (f 0 ) and corresponding greater values of alluvium thickness (H), thus indicating a greater seismic risk triggered by soil amplification in the study area. The findings of the study showed complete agreement with the research studies conducted by Field and Jacob (1995), Lachet et al (1996), Parolai et al (2002), and Panou et al (2005), (Bala et al 2007a, b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study area reflects a high variability in terms of fundamental frequency f 0 and alluvium thickness H. Overall results reflect low values of fundamental frequency (f 0 ) and corresponding greater values of alluvium thickness (H), thus indicating a greater seismic risk triggered by soil amplification in the study area. The findings of the study showed complete agreement with the research studies conducted by Field and Jacob (1995), Lachet et al (1996), Parolai et al (2002), and Panou et al (2005), (Bala et al 2007a, b).…”
Section: Discussionsupporting
confidence: 90%
“…Many scientists such as Chávez-García et al (1990, Bard (1999), Bour et al (1998) have utilized H/V and proven the reliability and credibility of this technique. H/V method is a very reliable method for estimating alluvium thickness by means of fundamental frequencies of the soft sediments (Morales et al 1991;Yamanaka et al 1994;Parolai et al 2002;Panou et al 2005). Contrary to the fundamental frequency f 0 , amplification factor A 0 reveals disagreement between opinions and findings of different scientists.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, and as reported in various other studies (e.g. Parolai et al 2004;Panou et al 2005;Guillier et al 2007), the shape and amplitude of the H/V curves remains fairly constant.…”
Section: Amplitude Spectrasupporting
confidence: 74%
“…This has also been observed during longer-term deployments of single stations for H/V measurements (Parolai et al 2004;Panou et al 2005;Guillier et al 2007). Nevertheless, consistent with the findings in this study, the derived H/V peak frequencies are reported to be stable with time.…”
Section: Amplitude Spectrasupporting
confidence: 56%
“…In addition, variations in the relative content of Love and Rayleigh waves could explain the observed temporal variations in measured H/V amplitudes (e.g. Panou et al, 2005b). …”
Section: Introductionmentioning
confidence: 98%